Evaluation of emergency department utilization for dermatologic conditions in the pediatric population within the United States from 2009‐2015. Issue 2 (18th December 2020) - Collier, Erin K.; Yang, Jason J.; Sangar, Sophia; Chen, Steven T.; Huang, Jennifer T.; Bach, Daniel Q.
Abstract: Background: Dermatologic conditions comprise a significant number of emergency department visits in the pediatric population in the United States. Understanding key predictors of emergency department utilization for dermatologic conditions is important to reduce inappropriate use. Methods: A total of 44 554 sampled patient emergency department visits, consisting of patients less than 18 years of age, were collected from the National Hospital Ambulatory Medical Care Survey between 2009 to 2015. ICD‐9 codes were used to define dermatologic conditions versus non‐dermatologic conditions with univariate and multivariate analyses used to identify factors significantly correlated with dermatologic emergency department utilization. Results: A total of 13 681 691 pediatric dermatologic emergency department visits (weighted) were evaluated over the seven‐year period, representing 6.4% of total pediatric emergency department visits. The most common dermatologic diagnosis was cellulitis (25.6% of visits). The majority of patients were five years old or younger (54.4%). Patients with primary dermatologic conditions were more likely to be triaged as non‐urgent (16.7%) or semi‐urgent (45.8%) than patients without dermatologic conditions. Only 2.1% of patients with dermatologic conditions required further observation or admission. On further regression modeling, age ≤ 5, semi‐urgent or non‐urgent acuity, Medicaid insurance, and residence in the Northeastern or Midwestern United States were significantly associated with presentation to the emergency department with a dermatologic condition when compared to non‐dermatologic condition. Conclusions: Dermatologic conditions continue to comprise a significant number of ED visits in the pediatric population. Increased ED utilization by vulnerable pediatric populations highlights the need to better direct or provide access to outpatient dermatologic care.